Synthesis of molecular species for nanotechnological applications - Salesiotis, Christos (2013)
This thesis details the synthesis of molecular species designed for a variety of nanotechnological applications. The first chapter gives a brief introduction to nanotechnology and explains the concepts of supramolecular chemistry and self-assembly which are the basis on which this project is built. Special attention is given to non-covalent bonding interactions such as hydrogen-bonding and π- π interactions which drive the formation of complex architectures. The discussion is followed by many examples from the literature describing work that has been accomplished in various fields of supramolecular chemistry. The second chapter describes the synthesis, characterization and surface deposition studies of 1,4-diphenyl-1,3-butadiyne-3,3’-5,5’-tetracarboxylic acid (DPBDTC). Recent work on surface deposition studies of terphenyl-tetracarboxylic acid (TPTC) has shown the formation of a 2D network that resembles an aperiodic tiling structure that shows orientational order but no translational symmetry. DPBDTC was designed in order to improve the aperiodic characteristics of the network formed. An experimental exploration of the phase space of interacting random tilings was also possible using the network obtained from DPBDTC deposited from nonanoic acid along with networks obtained with different molecules and under different conditions. The third chapter focuses on the synthesis, characterization and surface deposition studies of a series of porphyrin molecules functionalised with isophthalic acid and ferrocene groups at the meso-positions. The isophthalic acid groups are incorporated to encourage intermolecular interactions while the ferrocene groups are designed as potential carriers of binary information in the form of the redox states of the iron center. The above molecules were designed in order to study their potential use in molecular memory systems. The series of molecules consisted of porphyrins having the acetylene spacer in various positions. The diethyl-ester protected derivatives of the carboxylic acids and their zinc and magnesium metal complexes were studied using spectroelectrochemistry in order to reveal the qualitative redox properties of these systems. The fourth chapter discusses the design, synthesis and characterization of a series of metallated homoleptic and heteroleptic dypyrrinato complexes, using the dipyrrin 5-ethynyl-ferrocenyl dipyrrin. These molecules were synthesized with the prospect of validating the role of such complexes as a part of a dye or an electrolyte in dye-sensitized solar cells. Electrochemical and spectroelectrochemical studies in solution were also performed.